Mengenalkan Potensi Wisata Oleh Kelompok Tani Bumi Sinar Mukti Di Desa Ciporeat Kecamatan Cilengkrang Kabupaten Bandung - Meiyanti Nurchaerani; Alfian; Syahiid Hidayatullah Rizkyka Hartadhi (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The Bumi Sinar Mukti Farmers Group in Ciporeat Village has quite large tourism potential, such as livestock tourism, agricultural tourism, nature tourism. This tourism potential can improve the village economy and open up new job opportunities for the local community. In developing tourism potential, farmer groups can carry out strategies such as building homestays, improving the quality of livestock and agricultural products, and marketing products to tourists. Apart from that, farmer groups can also collaborate with the government, non-governmental organizations, or investors to develop tourism potential in Ciporeat Village. This report also includes tips for managing natural tourism potential in regions and tourist destinations based on sustainable tourism in Indonesia.